Potential of Freshly Fallen Elaeocarpus ganitrus Leaves as a Sustainable Ecoprint Biomaterial - Kristiana Dita Maharani; Widowati Widowati (Journal of Creativity Student, 2026)
The textile industry continues to face environmental challenges due to the intensive use of synthetic dyes and chemical processing, encouraging the exploration of sustainable biomaterials for textile production. Ecoprint has emerged as an environmentally friendly textile coloration technique; however, most studies still rely on fresh leaves harvested directly from plants. This study aimed to describe the ecoprint production process using newly fallen Elaeocarpus ganitrus leaves and to evaluate the quality of the resulting ecoprints. A descriptive quantitative approach with a comparative design was employed using five treatment variants: fresh leaves, untreated newly fallen leaves, steamed newly fallen leaves, vinegar-treated newly fallen leaves, and alcohol-treated newly fallen leaves. Ecoprints were produced on silk-cotton fabric using the steam ecoprint technique. Product quality was evaluated by seven expert panelists based on five indicators: motif clarity, sharpness of leaf vein detail, color intensity, color evenness, and overall aesthetic quality. Data were analyzed using descriptive statistics and the Friedman test. The results showed that all treatment variants produced ecoprints with good to very good quality. Untreated newly fallen leaves achieved the highest overall mean score (4.08), whereas steamed leaves recorded the lowest (3.91). However, the Friedman test indicated no statistically significant differences among treatments across all quality indicators (p > 0.05). These findings demonstrate that newly fallen Elaeocarpus ganitrus leaves can be directly utilized as an alternative ecoprint biomaterial without requiring additional pre-treatment, thereby simplifying the production process while supporting more sustainable utilization of local plant biomass.